The Development of Maritime Culture in the Islamic Mataram Kingdom: Social, Ekonomic, and Political Dynamics During the Time of Sultan Agung (1613 – 1645 AD) - Muhsin, Imam; Maharsi, Maharsi; Faidi, Ahmad; Latifah, Zuhrotul; Ittihadiyah, Himayatul; Syauqii, Fachri; Al Hamid, Mujahidin Nur (Diakronika, 2025)
This research examines the development of maritime culture in the Islamic Mataram Kingdom during Sultan Agung (1613-1645 AD), focusing on the interaction between agrarian and maritime cultures that shaped the Kingdom's identity. The Islamic Mataram Kingdom, located in the interior of Java, not only developed agrarian power but also made maritime expansion efforts as its power base. Through a historical approach using political and cultural analyses of primary sources, such as Babad Tanah Djawi, with the concepts of continuity and change as well as cultural acculturation as the basis for understanding the social dynamics that occurred, this research explores Sultan Agung's various policies, including the development of port infrastructure, the strengthening of the navy, and the development of religious traditions related to the sea. The results show that these policies expanded trade routes and strengthened the Kingdom's social and political legitimacy. By integrating local culture and Islamic elements, Sultan Agung created a synergy between agrarian and maritime power, significantly impacting Mataram society's economic and social stability. The findings are expected to provide new insights into the role of marine culture in Indonesian history, which is inclusive, cosmopolitan, multicultural, intercultural/mutual cooperation, and egalitarian, and its relevance in the context of marine culture development today.